TRADISI REBU DALAM BUDAYA BATAK KARO (STUDI KASUS: MASYARAKAT KARO PERANTAU DI KORA PADANG) - Marco Yesky Ivanta Sebayang; Sri Meiyenti; Hairul Anwar (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Rebu is a tradition of the Karo people that imposes restrictions on speaking, touching, and being in the same room with parents-in-law, sons-in-law, or siblings-in-law after marriage. This tradition aims to maintain the harmony of kinship relationships formed through marriage. This study aims to describe the kinship relationships between in-laws in Karo families in Padang City and to depict the changes in rebu practices there. This research uses a descriptive qualitative method with data collection techniques including observation, in-depth interviews, literature study, and documentation. Informants were selected using the snowball sampling technique, consisting of six key informants and five supporting informants. Data analysis utilized the concepts of avoidance relationship and joking relationship, as well as cultural contact theory. The findings indicate that the rebu tradition in Padang City has undergone changes. The practice of rebu among the Karo community in Padang is not as strict as it is in Karo Regency. Reasons for these changes include a lack of social control and the more relaxed urban lifestyle, such as living together in the same house or the necessity of greeting each other during certain moments. The practice of rebu in the hometown differs from that in Padang City because the Karo community in Padang has started to abandon this tradition due to the absence of strong social control from the local Karo community.